Performance of real-time polymerase chain reaction in the detection of infectious bursal disease virus - Hamzah, Hairul Aini; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini (Universiti Putra Malaysia Press, 2004)
The sensitivity of SYBR Green 1 based real-time PCR to detect infectious bursal disease virus (IBDV) was compared with an ELISA nested RT-PCR and conventional gel electrophoresis methods. The real-time PCR was at least 10 fold more sensitive than the ELISA nested RT-PCR, while the ELISA nested PCR was at least 10 fold more sensitive than the conventional gel electrophoresis. Thus, real-time PCR using SYBR Green 1 offers a sensitive, rapid and convenient method for screening large number of IBDV.